2008
DOI: 10.1103/physrevb.78.214419
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic transitions and spin dynamics in the3d1systemK2NaCrO8investigated by magnet

Abstract: We report pulsed magnetization and 23 Na NMR studies of a quantum phase transition and its associated spin dynamics in a 3d 1 system, using the alkali-metal peroxychromate K 2 NaCrO 8 . This is an example of a Cr 5+ -based S =1/ 2 and I ϳ 0 material with a clearly defined T N = 1.7 K in zero applied field ͑H͒. Its magnetization ͑M͒ shows a nonlinear increase with H, in contrast to a simple three-dimensional antiferromagnet, and saturates at H C = 7.4 T. This easily accessible H C allows for a detailed study by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Cr 5+ in K2NaCrO8. The labels for the atoms is the same as used by Cage and Dalal 14 and the J1 and J2 designations are the same as used by Choi et al 18 Label Cr• • • Cr ( Å) Pathway J1…”
Section: Table I: Possible Magnetic Exchange Pathways Betweenmentioning
confidence: 99%
See 4 more Smart Citations
“…Cr 5+ in K2NaCrO8. The labels for the atoms is the same as used by Cage and Dalal 14 and the J1 and J2 designations are the same as used by Choi et al 18 Label Cr• • • Cr ( Å) Pathway J1…”
Section: Table I: Possible Magnetic Exchange Pathways Betweenmentioning
confidence: 99%
“…These signatures indicate the presence of low dimensional antiferromagnetic behavior and the onset of long-range antiferromagnetic ordering. More recently, Choi et al 18 performed low temperature magnetization and 23 Na NMR measurements and identified a quantum phase transition from an antiferromagnetically ordered state to a ferromagnetically polarized state at critical field H c of about 7.4 T, with β = 0.44 ± 0.05 in H = 5 T and β = 0.53 ± 0.05 in H = 6.8 T. Since mean-field theory yields β = 1/2 for magnetization, these workers concluded that the high field magnetization of K 2 NaCrO 8 is mean-field-like.…”
mentioning
confidence: 97%
See 3 more Smart Citations